Current Surgical Interventions for Treating Tuberculosis: Exploring the Benefits and Risks - Kardani, Sunil (Asian Journal of Pharmaceutics (AJP), 2023)
The main organs affected by the chronic infectious disease tuberculosis (TB) are the lungs. Although the main form of therapy for TB is medicinal, surgical intervention may be necessary if the disease is localized to a particular area of the lung and cannot be effectively treated with medicines alone. Segmentectomy, pneumonectomy, and lobectomy are the three primary surgical procedures used to treat TB, and video-assisted thoracoscopic surgery, a minimally invasive technique, enables the removal of the diseased tissue. The surgical removal of one of the five lung lobes is known as a lobectomy. When TB is limited to one lobe of the lung and cannot be adequately treated with medication alone, surgery is often undertaken. Candidates for lobectomy include patients with cavitary lesions larger than 4 cm, a persistent cough, fever, hemoptysis, bronchopleural fistula, or localized abscess formation. The risk of problems can be reduced with appropriate pre-operative assessment, surgical technique, and post-operative care. The surgical removal of the complete lung is known as a pneumonectomy. It is normally saved for TB cases where medicine is ineffective and the disease has spread to affect a significant area of the lung. Pneumonectomy may be an option for patients who have severe cavitary lesions, extensive lung damage, considerable main bronchus involvement, or consequences including bronchopleural fistula, severe hemoptysis, or localized abscess formation. Similar to lobectomy, the risk of problems can be reduced with good pre-operative assessment, surgical technique, and post-operative care. A segment of a lung lobe is surgically removed, a procedure known as a segmentectomy or partial lobectomy. When TB is confined to a particular area of the lung and cannot be properly treated with drugs alone, surgery may be an option. Segmentectomy may be beneficial for patients with a tiny cavitary lesion, localized fibrosis, or a cavitary lesion that cannot be removed in the upper lobe of the lung or who are unable to have more comprehensive surgery. Once more, minimizing the risk of problems can be achieved through good pre-operative assessment, surgical technique, and post-operative care.